Testes rápidos de qualidade tecnológica industrial para seleção de linhagens de trigo - Rosa, Ana Claudia (2019)
Baking quality and grain yield are the main selection parameters in wheat improvement. In this sense, the selection via rapid tests directed to both the high productive potential of grains and the quality of flour for baking should be intensified by breeding programs. The objective of this study was to identify superior wheat strains, in agronomic traits and industrial quality, in the Genetic Improvement Program of UTFPR, for the possible release of cultivars. 24 strains and 4 controls were evaluated in trials of value of use crop (VCU) year 1 and 2, in the 2017 crop in the environments of Renascença – PR, Itapejara – PR and Clevelândia – PR in VCU1 and Renascença – PR, Itapejara – PR and Clevelândia – PR, Pato – Branco PR e Campos Novos – SC in VCU 2. The evaluated traits were: grain yield, hectoliter weight, sodium dodecyl sulfate sedimentation, lactic acid retention capacity and water retention capacity. The data were submitted to analysis of variance, and verifying significant effects for test f, means were compared by Scott-Knott (p <0.05); in addition, performed Pearson's correlation, and the optimal genotype analysis. The results showed that the parameters evaluated have a significant GxA interaction. UTFT lines 15895 and UTFT 140481 were tested in VCU1, UTFT 141463, UTFT 140542, UTFT 141506 and UTFT 141620 assays in VCU2 assay. There was a significant correlation, between medium and strong magnitude, between grain yield and hectoliter weight, water retention capacity and sedimentation to sodium dodecyl sulfate, lactic acid retention capacity and hectoliter weight. In this way, it is possible to infer that the tests performed are efficient in the selection of wheat strains.